Quality of life among Iranian patients with beta-thalassemia major using the SF-36 questionnaire - Haghpanah, Sezaneh; Nasirabadi, Shiva; Ghaffarpasand, Fariborz; Karami, Rahmatollah; Mahmoodi, Mojtaba; Parand, Shirin; Karimi, Mehran (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Patients with beta-thalassemia major (β-TM) experience physical, psychological and social problems that lead to decreased quality of life (QoL). The aim here was to measure health-related QoL and its determinants among patients with β-TM, using the Short Form-36 (SF-36) questionnaire. DESIGN AND SETTING: Cross-sectional study at the Hematology Research Center of Shiraz University of Medical Sciences, in southern Iran. METHODS: One hundred and one patients with β-TM were randomly selected. After the participants’ demographics and disease characteristics had been recorded, they were asked to fill out the SF-36 questionnaire. The correlations of clinical and demographic factors with the QoL score were evaluated. RESULTS: There were 44 men and 57 women of mean age 19.52 ± 4.3 years (range 12-38). On two scales, pain (P = 0.041) and emotional role (P = 0.009), the women showed significantly lower scores than the men. Lower income, poor compliance with iron-chelating therapy and presence of comorbidities were significantly correlated with lower SF-36 scores. These factors were also found to be determinants of worse SF-36 scores in multivariate analysis. CONCLUSIONS: We showed that the presence of disease complications, poor compliance with ironchelating therapy and poor economic status were predictors of worse QoL among patients with β-TM. Prevention and proper management of disease-related complications, increased knowledge among patients regarding the importance of managing comorbidities and greater compliance with iron-chelating therapy, along with psychosocial and financial support, could help these patients to cope better with this chronic disease state.